Current indications of free gingival grafts - Márcio Zaffalon Casati; Francisco Humberto Nociti Junior; Enilson Antonio Sallum; Mauro Pedrini Santamaria; Daniela da Silva Feitosa; Sérgio Toledo (Faculdade São Leopoldo Mandic, 2008)
The aim of this report is to show three cases treated by the free gingival graft technique. Two patients presented multiple andisolated Miller's Class II and III gingival recessions, localized in the anterior region of mandible. The third patient showed absence ofqueratinized gingiva on the buccal aspect of an osseointegrated implant. All patients received free gingival grafts, and the palate was the donor area. The patients were followed up to one year. After the healing period, all cases showed an increase of the queratinized gingival width and, in cases 1 and 2, a reduction in gingival recession. During follow-up period, no signs of gingival inflammation and bleeding on probing were seen. The patients maintained appropriate plaque control and were satisfied with the final esthetics. This report indicates that free gingival graft technique can be used for successful treatment of multiple and isolated gingival recessions, as well as to increase periimplantar queratinized gingival width.